Integrated geochemical and geophysical monitoring for the assessment of natural pollutant mitigation in heavy metal-contaminated areas of South Korea, Deagu - Seo Young Song; Sunjae Lee; Heuisoon Lee; Myung Jin Nam; Choi, Jae Young (Springer Verlag, 2024)
The evaluation and monitoring of sites contaminated with heavy metals are essential for pollution remediation and prevention. In this study, we conducted geophysical and geochemical investigations at a site exhibiting heavy metal contamination downstream from an abandoned mine, with the aim of analyzing the extent of contamination and its temporal variation. We employed geophysical survey methods including electrical resistivity and induced polarization surveys of areas contaminated with heavy metals. Repeated surveys were conducted over time using the electrical resistivity method. Numerical simulations were employed to mitigate and eliminate electrical noise stemming from topography on the site. Additionally, time-lapse inversion was conducted on the resistivity data sets to analyze the changes in resistivity caused by variations in heavy metal contaminants. In the geochemical survey, soil samples were collected from the same locations as the geophysical survey, and chemical properties including pH, water content, electrical conductivity, and cation exchange capacity were analyzed. Our results showed that with the reduction of major sources of As and Zn contamination by 50%, the time-lapse electrical resistivity inversion results indicated that the resistivity of the subsurface materials increased by a factor of two. This paper demonstrated the natural reduction of the heavy metal contaminants at the site due to rainfall, aiming to comprehensively analyze the resultant alteration of both geochemical and geophysical properties.